2014
DOI: 10.5194/acp-14-9481-2014
|View full text |Cite
|
Sign up to set email alerts
|

Downslope föhn winds over the Antarctic Peninsula and their effect on the Larsen ice shelves

Abstract: Abstract.Mesoscale model simulations are presented of a westerly föhn event over the Antarctic Peninsula mountain ridge and onto the Larsen C ice shelf, just south of the recently collapsed Larsen B ice shelf. Aircraft observations showed the presence of föhn jets descending near the ice shelf surface with maximum wind speeds at 250-350 m in height. Surface flux measurements suggested that melting was occurring. Simulated profiles of wind speed, temperature and wind direction were very similar to the observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 36 publications
4
60
0
1
Order By: Relevance
“…Recent research includes the documentation of föhn events in the Smoky Mountains (Gaffin, 2002), Japan (Takane & Kusaka, 2011), the Alps , the Appalachian Mountains (Gaffin, 2007;, the American Rockies (Oard, 1993), the Antarctic Dry Valleys (Speirs et al, 2010;Steinhoff et al, 2013; and the Antarctic Peninsula (Elvidge et al, 2014a;2014b;Grosvenor et al, 2014). Being found in such widely diverging geographical locations has resulted in a number of local names for the föhn wind, including the Chinook (American Rockies), the berg wind (South Africa), Santa Ana winds (California), the Zonda (Andes) and the Nor'wester (New Zealand) (among many others, see Richner & Hächler, 2013).…”
Section: Föhn Wind Classification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research includes the documentation of föhn events in the Smoky Mountains (Gaffin, 2002), Japan (Takane & Kusaka, 2011), the Alps , the Appalachian Mountains (Gaffin, 2007;, the American Rockies (Oard, 1993), the Antarctic Dry Valleys (Speirs et al, 2010;Steinhoff et al, 2013; and the Antarctic Peninsula (Elvidge et al, 2014a;2014b;Grosvenor et al, 2014). Being found in such widely diverging geographical locations has resulted in a number of local names for the föhn wind, including the Chinook (American Rockies), the berg wind (South Africa), Santa Ana winds (California), the Zonda (Andes) and the Nor'wester (New Zealand) (among many others, see Richner & Hächler, 2013).…”
Section: Föhn Wind Classification Methodsmentioning
confidence: 99%
“…Climate of the Antarctic Peninsula (OFCAP) project (Elvidge et al, 2014a;2014b) and have been shown to have major implications on regional warming and nearsurface energy and mass balances of ice sheets (Kuipers Munneke et al, 2012;Grosvenor et al, 2014;Luckman et al, 2014). The displacement of the circumpolar westerlies is also thought to be responsible for the recent cooling found on the interior of the Antarctic continent (Comiso, 2000).…”
Section: The Circumpolar Vortex and The Southern Annular Modementioning
confidence: 99%
“…The isentropic drawdown of this warm air could therefore explain a large part of the foehn warming observed. In Antarctica, this type of foehn warming (nonlinear foehn event) has been observed on the east side of the AP (Elvidge et al 2015Cape et al 2015;Grosvenor et al 2014) and in the McMurdo dry valleys of EA (Speirs et al 2010;Steinhoff et al 2013Steinhoff et al , 2014. We cannot, however, ignore the contribution of the latent heating of precipitation.…”
Section: Atmospheric Process Responsible For Warm Eventsmentioning
confidence: 99%
“…The summer warming of the AP over the last half of the 20th century, for example, is consistent with strengthened westerly marine air advection driven by changes in the Southern Hemisphere Annular Mode (SAM) (e.g., Marshall et al 2006;Turner et al 2016). This warm westerly flow travels over mountain ranges on the AP, causing additional temperature increase by adiabatic warming as the air descends on the east side of the AP that is called a foehn warming (e.g., Elvidge et al 2015Cape et al 2015;Grosvenor et al 2014). The increase in poleward marine air advection is also known to have contributed to summer warming at Byrd Station through most of the late 1980s, though it can not solely explain long-term trends in West Antarctica (Bromwich et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Como es bien conocido, el efecto föhn no produce lluvias per sé (Grosvenor et al, 2014;Nastos et al, 2017;van Drooge & Ballesta, 2010). El término föhn se refiere estrictamente al ejemplo de los Alpes europeos, aunque tiene diferentes nombres en distintas regiones del mundo: en Málaga y Cádiz se denomina terral (aunque en Málaga sea de componente noroeste y en Cádiz de noreste).…”
Section: Introductionunclassified